The friction force between the soccer ball and the goalkeeper glove material - Sasaki, R.; Hong, S.; Sakamoto, K.; Nakayama, M.; Asai, T. (Procedia Engineering, 2014)
Some previous studies have reported the consistency of the model calculations of the impact force, angle of reflection, coefficient of restitution, and the ball speed and angular velocity after impact. The others have reported the theoretical analyses of the effect of friction for impact if the ball and the flat surface have friction, or not. But only few data from the previous research have reported the experimental measurement of the impact of the soccer ball, which is pressurized spherical elastic shell, against the flat surface which has friction. This study is primarily intended to find out the property of the characteristics of the friction force which is formed by the collision of the soccer ball against the materials used for the goalkeeper gloves, changing the impact speed from 10 to 30 m/s. The soccer balls shot out by the 3 rotors machine keep the angular velocity 0 and come into collision on the angle with the rectangular-shaped latex formed material used for the goalkeeper gloves on the force plate. The impact force is measured vertically and horizontally from the force plate. Getting the averaged impact force curves, we discussed about the feature of the friction force between the soccer ball and the latex formed material. In addition, we measured the surface texture of the latex formed material by using the laser displacement meter, and discussed the relationship between the friction force and the surface texture.